Assessment question generator for O-level elementary mathematics : for the topic of ratio, rate and proportion - Shi, Qing. (2012)
In Singapore, countless mathematics hardcopy assessment books are available in the bookshops mainly cater for secondary students in preparing for GCE Ordinary-Level (O-Level) mathematics examination. Many students invest lots of money in these assessment books just for having more practice in different types of question. In fact, each assessment book can only provide limited questions and some of the assessment books are providing the same questions. Thus, students have to consume more time and money in searching the useful assessment books. Mathematics is one of the subjects that need more practice to obtain a higher grade.